2017
DOI: 10.1007/s10530-017-1440-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the invasive bryozoan Schizoporella japonica in Great Britain and Ireland and a review of its European distribution

Abstract: The bryozoan Schizoporella japonica Ortmann (1890) was first recorded in European waters in 2010 and has since been reported from further locations in Great Britain (GB) and Norway. This paper provides a new earliest European record for the species from 2009, a first record from Ireland and presence and absence records from a total of 231 marinas and harbours across GB, Ireland, the Isle of Man, France and Portugal. This species is typically associated with human activity, including commercial and recreational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A sub-group of cheilostomes that feature both a wide geographical range and a corresponding wide range in mineralogy are those that have become successful as non-native (alien) species. An example from this study is Schizoporella japonica a species which was first found in Scotland in 2011 [ 94 ] and has since been found to inhabit marinas and harbours across Scotland and further afield [ 95 ]. This species has been reported from Norway to Malaysia and has highly plastic skeletal mineralogy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A sub-group of cheilostomes that feature both a wide geographical range and a corresponding wide range in mineralogy are those that have become successful as non-native (alien) species. An example from this study is Schizoporella japonica a species which was first found in Scotland in 2011 [ 94 ] and has since been found to inhabit marinas and harbours across Scotland and further afield [ 95 ]. This species has been reported from Norway to Malaysia and has highly plastic skeletal mineralogy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…During this study, six NNS were identified at marinas and harbours; none were recorded at wave and tidal testing sites. However, NNS have been recorded on MREDs moored in harbour settings (Ryland et al 2014;Loxton et al 2017; Want, personal observations [ Figure 5]). This suggests that M 0 , zeroth moment is the area under the spectrum; M 1 , 1st moment is the mean; M 2 , 2nd moment is the SD; M 3 , 3rd moment is the skewness; M 4 , 4th moment is the kurtosis (Sokal & Rohlf 1995).…”
Section: Analysis Of Emec Waverider Buoy Field Datamentioning
confidence: 99%
“…The category was further divided into the sub-categories: invasive species and biosecurity, relating to the risk of invasive species presence and spread on fouled MRE devices and gaps and issues relating to biosecurity (13); the gaps in ecological knowledge of biofouling species and communities (9); and the gaps in understanding of potential positive and negative artificial reef effects of fouled MRE devices (5).…”
Section: Figure 3: Categorisation Of Notesmentioning
confidence: 99%
“…Non-native species are a known component of the biofouling assemblages on marine renewable energy device prototypes [52,13,12], and some non-native species are tolerant to biocidal antifouling coatings [53,54]. The fact that devices can provide habitat for fouling non-native species highlights the potential for devices to aid their spread to new locations through larval dispersal via the stepping stone effect [55] and through the wet movement of devices [12].…”
Section: Invasive Species Risk and Biosecuritymentioning
confidence: 99%
See 1 more Smart Citation